Correlation Between Glycosylated Haemoglobin And Plasma Glucose Levels For The Diagnosis And Control Of Diabetes Mellitus At A Tertiary Care Hospital In Western Rajasthan, india. (Global Journal of Medical Research, 2015)
Conventional methods are inadequate, unreliable, cumbersome and impractical to monitor continuous 24 hours blood glucose level, to overcome this problem development of new test detecting Glycosylated Haemoglobin (HbA1c), indicates plasma glucose level in last 3 months duration hence it is satisfactory tool for assessment of diabetic control. Therefore the present study is planned to know about the glycaemic control of diabetic patient by HbA1c and to know about the various complications. Objectives: To find correlation of Glycosylated Haemoglobin with fasting and post-prandial plasma glucose levels for the diagnosis and control of Diabetes Mellitus. Material and Methods: A hospital based Cross sectional study was conducted at chemical pathology section of Department of Pathology, Mahatma Gandhi and Mathura Das Mathur Hospital, affiliated to Dr. S. N. Medical College, Jodhpur. One hundred diabetic patients attending medical outpatient department of the same institution were included in the study. Results: Total one hundred confirmed diabetic patients with mean age 55.7±12.9 years and sex ratio of 1.85 in favor of males, were included in the study. Among both type of diabetics we found that fasting and post prandial plasma glucose levels had linear relationship with level of glycosylated Haemoglobin and on regression analysis this result was found statistically significant(p
Keywords: glycosylated haemoglobin; plasma glucose; correlation